Efficacy of combination therapy with GABA, a DPP-4i and a PPI as an adjunct to insulin therapy in patients with type 1 diabetes - Rabinovitch, Alexander; Koshelev, Daniil; Lagunas-Rangel, Francisco Alejandro; Kosheleva, Liudmila; Gavra, Tali; Schiöth, Helgi B.; Levit, Shmuel (Frontiers in Endocrinology, 2023)
Introduction The purpose of this retrospective clinic chart review study was to determine the potential of a combination therapy (CT) consisting of γ-aminobutyric acid (GABA), a dipeptidyl peptidase-4 inhibitor (DPP-4i), and a proton pump inhibitor (PPI) to improve glycemic control as an adjunct to insulin therapy in patients with type 1 diabetes (T1D). Research design and methods Nineteen patients with T1D on insulin therapy were treated with additional CT in oral form. Fasting blood glucose (FBG), HbA1c, insulin dose-adjusted HbA1c (IDA-A1c), daily insulin dose, insulin/weight ratio (IWR), and fasting plasma C-peptide were measured after 26-42 weeks of treatments. Results FBG, HbA1c, IDA-A1c, insulin dose and IWR were all significantly decreased while plasma C-peptide was significantly increased by the CT. Treatment outcomes were further analyzed by separation of the 19 patients into two groups. One group started on the CT within 12 months of insulin treatment (early therapy, 10 patients) and another group started on this therapy only after 12 months of insulin treatment (late therapy, 9 patients). FBG, IDA-A1c, insulin dose, and IWR decreased significantly in both the early and late CT groups, however to a better extent in the early therapy group. Moreover, plasma C-peptide increased significantly only in the early therapy group, and 7 of the 10 patients in this group were able to discontinue insulin treatment while maintaining good glycemic control to study end compared with none of the 9 patients in the late therapy group. Conclusion These results support the concept that the combination of GABA, aDPP-4i and a PPI as an adjunct to insulin therapy improves glycemic control in patients with T1D, and that the insulin dose required for glycemic control can be reduced or even eliminated in some patients receiving this novel therapy.